Changes and significance of 25-hydroxyvitamin D levels in patients with type 2 diabetic nephropathy - ZENG Yan; ZHAO Shao-jing; LI Zheng-dong (Linchuang shenzangbing zazhi)
Objective To investigate the values of 25-hydroxyvitamin D [25(OH)D]in patients with type 2 diabetic nephropathy.Methods From August 2014 to February 2018,used the convenient sampling and retrospective research methods,180 patients with diabetic nephropathy diagnosed and treated by Department of Nephrology,Dongfeng Hospital affiliated to Hubei Medical College were selected as subjects and were to investigate the clinical data of patients.The patient’s serum25(OH)D,urinary albumin excretion rate(UAER)levels were recorded,and the patient’s condition were recorded and analyzed for correlation.The UAER≥300 mg/24 h were indicated the presence of diabetic nephropathy;UAER≥30 mg/24 h were indicated the presence of microalbuminuria.Results There were 50 patients of microalbuminuria,20 patients of massive proteinuria;average serum25(OH)D level were(31.0±15.5)ng/mL,the serum25(OH)D level of large urine protein group were significantly lower than the other two groups(P<0.05).There were 120 patients in the normal group of vitamin D,40 patients in the inadequate group and20 patients in the lack group.The UAER in the vitamin D deficiencygroup were significantly higher than the other two groups(P<0.05).There were also significant differences in serum creatinine,high-density lipoprotein cholesterol(HDL-C)and triglyceride(TG)compared between the three groups(P<0.05).Pearson correlation analysis showed that serum25(OH)D levels in patients with diabetic nephropathy were significantly negatively correlated with UAER and serum creatinine(P<0.05),and were significantly positively correlated with HDL-C(P<0.05).Stepwise regression analysis found that serum creatinine and UAER were independent factors taht affected serum25(OH)D levels(P<0.05).Conclusions Serum25(OH)D are low level in patients with type 2 diabetic nephropathy that have significant correlation with serum lipids and UAER,which may affect the patient’s disease progression and have good clinical values.